Growth and Financial Profiles Amongst Manufacturing SMEs from Australia's Business Longitudinal Survey - McMahon, Richard G. P. (Entrepreneurship Theory and Practice, 2001)
The principal objective of this paper is to compare and contrast financial profiles for a longitudinal panel of 871 small and medium-sized enterprises (SMEs) In the Australian manufacturing sector that have embarked upon different development pathways and to examine possible connections between enterprise growth and the experience of common financial problems. Collectively, the findings represent a departure from much received knowledge in SME financial scholarship. The experience of growth seems not to have influenced the return on Investment, asset structure, financial structure, liquidity and solvency ratios of the SMEs studied; but the margin, operating expenses, turnover, and financing expense ratios do appear to be affected by growth. Overall, the financial profiles produced are quite unremarkable; there Is no evidence of problematic financial consequences of growth. The only differences in financial profiles found are those that are readily explained by differences in the scale or growth resource needs of the businesses examined.